The Course of Fatigue during the First 18 Months after First-Ever Stroke: A Longitudinal Study - Anners Lerdal; Kathryn A. Lee; Linda N. Bakken; Arnstein Finset; Hesook Suzie Kim (Stroke Research and Treatment)
Background. Little is known about the course of poststroke fatigue. Objectives. To describe the course of poststroke fatigue in relation to the patient's level of physical functioning, depressive symptoms, and self-reported history of prestroke fatigue. Methods. A longitudinal study using structured face-to-face interviews, questionnaires, and patients' medical records. Data were collected from 95 patients in Norway with first-ever stroke. Fatigue was measured with the Fatigue Severity Scale 7 item version and assessed for change between the acute phase, six, 12, and 18 months after stroke using 2-way ANOVA repeated-measures analyses. Results. The patients' level of fatigue did not change over time. However, those who reported prestroke fatigue showed a relatively high level of fatigue over time in the poststroke period, while patients with no history of pre-stroke fatigue showed a stable course of relatively low fatigue over time. Conclusion. Studies on poststroke fatigue should control for the patient's pre-stroke fatigue level.